ANALISIS PENGARUH PMA, PMDN, DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI JAWA TENGAH - Rianti Patriamurti; Yustirania Septiani (Universitas Teuku Umar, 2020)
Economic growth is one measure for economic development in an area that is reflected in the PDRB. Economic growth can be related to foreign investment, domestic investment and labor. This research is a quantitative research using panel data regression method. This study uses secondary data, namely time series data for five years in 2014 - 2018 and cross section data which is PDRB data, foreign investment (PMA), domestic investment (PMDN), and labor in 35 cities / districts in Province of Central Java. This study aims to look at the effect of foreign investment, domestic investment, and labor on economic growth in Central Java Province in 2014 - 2018. The results of this study state that Foreign Investment (PMA) has a negative and significant effect on economic growth in Central Java Province with a coefficient value of -3.665910. Domestic Investment (PMDN) has a positive and significant effect on economic growth in Central Java Province with a coefficient value of 0.245317. Labor (TK) has a positive and significant effect on economic growth in Central Java Province with a coefficient value of 163.7923. Simultaneously, Foreign Direct Investment (PMA), Domestic Investment (PMDN), and Labor affect the economic growth in Central Java Province in 2014 - 2018.Keywords : Domestic Investment (PMDN), Economic Growth, Foreign Investment (PMA), Labor.